Character Education in Islamic View: The Case of Ibn Tufayl's Hay ibn Yaqdzan Story - Alamin, Nurul Salis; Az-Zahra, Haninah; Puspita, Erva Dewi Arqomi (ISTAWA, 2023)
In this modern era, society is at a pivotal juncture regarding how its personality develops. There are a significant number of researchers, academics, and figures who advocate for character-based education. Many arguments have been made that cultivating moral character is the only way to progress as a nation. Islamic scholars have established a paradigm for character education throughout the lengthy history of Islamic traditions. This article sheds light on the character education model in Islamic tradition and heritage. This model is best demonstrated by the growth of Hayy ibn Yaqdzan in the story written by Ibn Tufayl. This study is qualitative library research in education. The primary and secondary data are referred to in books, articles, and other publications. The collected data are analyzed using descriptive analysis. This research uncovers, first, character education in Hayy ibn Yaqdzan's story following the Qur'an and Hadith. Second, the characters in the story of Hayy ibn Yaqdzan are developed through purifying the soul and a deep love for the pursuit of knowledge. In the third place, a good character will be more driven by a deep passion for being close to the Creator.